Mapping of Education Information Networks in Community of Cintaratu Village Pangandaran - Evie Ariadne Shinta Dewi; Nindi Aristi; Rachmaniar Rachmaniar (The Journal of Society and Media, 2020)
This article is based on the results of research which the aim is to find out how is mapping of the education information dissemination network in the community of Cintaratu village, Pangandaran district. The reason for choosing the topic was that Padjadjaran University (Unpad) campus is in the village and it is assumed that the presence of the university in the village could improve the quality of education of its people. To confirm this assumption, it is necessary to map the education sector information network. We use qualitative methods which approach is a descriptive study, the researchers conducted a mapping of educational information dissemination. The main informants of this study are the community and village officials. Data were collected through in-depth interviews, passive participatory observation, and literature studies. The finding of the research are as follows, 1) the initial mapping of educational information dissemination to the community was carried out through direct communication, namely through two major activities - recitation and celebration; 2) recitation and celebration are two activities that are susceptible to physical noise-causing information related to education not conveyed properly to the public. Effective communication does not occur in these two activities.